2018
DOI: 10.11604/pamj.2018.30.248.12464
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis of colorectal cancer in Zambia, Southern Africa using the National Cancer Disease Hospital Database

Abstract: IntroductionColon cancer is preventable. There is a plethora of data regarding epidemiology and screening guidelines, however this data is sparse from the African continent. Objective: we aim to evaluate the trends of colorectal cancer (CRC) in a native African population based on age at diagnosis, gender and stage at diagnosis.MethodsWe conducted a retrospective analysis of the Cancer Disease Hospital (CDH) registry in Zambia, Southern Africa.Results377 charts were identified in the CDH registry between 2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 9 publications
5
12
1
Order By: Relevance
“…Although, researchers generally agree that the burden of CRC in SSA will increase, the true incidence, prevalence and burden of CRC remain uncertain [2, 3]. This uncertainty has largely been attributed to the dearth of high-quality cancer registries and the limited number of studies [1, 4, 10]. Additional concern includes the possibility that data from existing registries is often suboptimal/partial or conflicting, hence, incomprehensive [4, 10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, researchers generally agree that the burden of CRC in SSA will increase, the true incidence, prevalence and burden of CRC remain uncertain [2, 3]. This uncertainty has largely been attributed to the dearth of high-quality cancer registries and the limited number of studies [1, 4, 10]. Additional concern includes the possibility that data from existing registries is often suboptimal/partial or conflicting, hence, incomprehensive [4, 10].…”
Section: Introductionmentioning
confidence: 99%
“…This uncertainty has largely been attributed to the dearth of high-quality cancer registries and the limited number of studies [1, 4, 10]. Additional concern includes the possibility that data from existing registries is often suboptimal/partial or conflicting, hence, incomprehensive [4, 10]. Corroborating this conclusion, trace-back of cancer deaths to obtain the corresponding hospital records has demonstrated that quality of diagnostic information on cancer cases is generally poor [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to early-onset CRC, CRC in individuals of African origin has been observed to develop at a relatively younger age 5,10,17,18 compared with white people. 19,20 Arguments on the difference in tumor biology and risk factors that place individuals of African descent at a relatively higher risk have been pointed out.…”
Section: Discussionmentioning
confidence: 99%
“…9 Exploring these factors in our communities may help address the increasing incidence and the observed trend of young individuals being affected by the disease. 5,8,10 Author affiliations and support information (if applicable) appear at the end of this article. We conducted a record review from 1998 to 2018 for patients with CRC in our center, with the aim of describing the burden of the disease, clinical characteristics of patients, and the extent of the disease at diagnosis.…”
Section: Introductionmentioning
confidence: 99%